PERAN LABA MEMPENGARUHI HUBUNGAN MODAL KERJA DAN BIAYA EKUITAS STUDI KASUS PADA PERUSAHAAN PROPERTI, REAL ESTATE DAN KONSTRUKSI BANGUNAN DI DAFTAR EFEK SYARIAH TAHUN 2008 - 2012 - PRASETYO ANI PUJIASTUTI, 1252020126; Sunarto, Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2014)
This research aims to test the influence of NIBE profit to capital working and equity cost, a case study to property company,real astate and building construction at syari’ah Effect’s List ( DES). The sample used in this research is a group of property company,real estate and building construction with company category which its share is always sold actively in DES as long as the supervision ( 2008 – 2012 ) ,the sample result sum based on the category is 19 company for 5 year long,secondary data gained from stock exchange ( IDX ) statistic yearly from 2008 – 2012, the analysis used in this research is multiple regression by using t – test hypothesis on the level of significance 5% ( α = 0,05 ) . The hypothesis result shows that NIBE profit and capitel working variable cash and claim significantly influenced theequity cost.this result identified thatboth variable affect the equity significantly. Keyword : NIBE profit, capital working ( cash and claim ) , equity cost